2017
DOI: 10.6063/motricidade.7697
|View full text |Cite
|
Sign up to set email alerts
|

Adaptação Humana ao Stress em Contextos Desportivos: Teoria, Avaliação, Investigação e Intervenção

Abstract: Não existem dúvidas acerca do facto dos fatores psicológicos desempenharem um papel fundamental no modo como os atletas se adaptam ao contexto desportivo bem como acerca da influência destes fatores no rendimento desportivo que os atletas obtêm ao longo das suas carreiras (Cox, Shannon, McGuire, & McBride, 2010;Hatzigeorgiadis, Zourbanos, Galanis, & Theodorakis, 2011;MacNamara, Button, & Collins, 2010). No entanto, existem muitas dúvidas acerca do modo como o "lado mental" interfere nesta adaptação e no sucess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Many researchers have discussed the significant relationship between emotion and cognition (Doron & Martinent, 2017;Martinent & Ferrand, 2007;Smith et al, 1988), as cognitive development can regulate competitive anxiety (Gomes, 2017). For example, Zhang et al (2018) directly tested the different cognitive functions that are thought to be impaired when performing under anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have discussed the significant relationship between emotion and cognition (Doron & Martinent, 2017;Martinent & Ferrand, 2007;Smith et al, 1988), as cognitive development can regulate competitive anxiety (Gomes, 2017). For example, Zhang et al (2018) directly tested the different cognitive functions that are thought to be impaired when performing under anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…In sum, filling an important gap in the literature (Nicholls et al, 2012;Wong et al, 2015;Gomes, 2017) by pursuing a comprehensively investigating of the process of adaptation to competitive stressors, this study sought to analyze (1) the mediating role of cognitive appraisal in the relationship between competitive stressors and emotional experience; and (2) the moderating role of competitive level in the relationship between competitive stressors, cognitive appraisal, and emotions (cf. Figure 1).…”
Section: The Moderating Role Of Competitive Levelmentioning
confidence: 99%
“…Some research that analyzed the relationship between emotions and performance in athletes (e.g., Lane et al, 2009Lane et al, , 2010 suggested that positive emotional and psychological states, such as happiness, calm, and confidence, were associated with optimal performance (achievement of an important goal), whereas negative emotional and psychological states (e.g., anger and confusion) were associated with a dysfunctional performance and failure to achieve an important goal. These studies allow an understanding of the factors involved in the process of adaptation to stress; however, it is difficult to capture the whole experience of stress just by analyzing parts of the adaptation process, which reinforces the importance of capturing this process in an integrated way (Nicholls et al, 2012;Wong et al, 2015;Gomes, 2017). Thus, this study aims to provide an integrative framework to understand adaptation to stressors on young athletes by taking an integrative analysis of competitive stressors, cognitive appraisal of a stressful situation, and the arising emotions of the stressful situation, considering, at the same time, the athletes' characteristics (i.e., competitive level) that can influence the cognitive processing of stressful situations and, consequently, the adaptation process.…”
Section: Introductionmentioning
confidence: 99%